The inclusive language at the Spanish university: the reproduction of the media confrontation - Guerrero Salazar, Susana (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The debate on inclusive language has found in the media and social networks a field that feeds back on it and where the Real Academia Española, sometimes as an institution and sometimes through its members in particular, is very active. However, it is not a debate that has great relevance in Spanish universities, at least if we compare it with what is happening in some Latin Americans. The objectives of this paper are, firstly, to assess the issue of inclusive language in Spanish-speaking universities and to investigate the reasons why this debate has come so late to Spanish universities and has not been given sufficient attention, despite the media hype it generates. Secondly, to analyse the causes of the discredit of the guides on non-sexist language, focusing on those made by linguists teaching in Spanish universities. Thirdly, to demonstrate how the polarisation of the media debate seems to be replicated in academic spaces without allowing for an in-depth analysis that could lead to an understanding between conflicting positions
Keywords: Inclusive language; Real Academia Española; Feminism; University